PERANAN MULTIKULTURALISME DALAM ISLAM - Ari Laso; Sri Rahayu; Nadiya (Jurnal Ilmu Pendidikan dan Sosial, 2022)
Indonesia, as a country with high cultural and religious diversity, faces challenges in maintaining social harmony amidst differences. This study aims to explore the role of multiculturalism and religion, especially Islam, in shaping national and state life. The method used is qualitative with a literature review approach, which allows researchers to collect, analyze, and synthesize various literatures relevant to the research topic. Data sources were obtained from secondary literature including scientific journals, books, research reports, and policy documents. Literature searches were carried out systematically using keywords such as "multiculturalism," "religion," "Islam in Indonesia," "interfaith harmony," and "diversity." The data obtained were analyzed using a thematic analysis approach, where the main themes related to the relationship between religion and multiculturalism were identified, grouped, and synthesized to draw conclusions. The results of the study indicate that multiculturalism and religion have an important role in maintaining social cohesion in Indonesia. Islam, as the majority religion, plays a central role in regulating and supporting cultural diversity through the values ​​taught in the Quran and Hadith. However, challenges arise due to differences in religious interpretations that can trigger fanaticism and radicalism, which threaten harmony between religious communities. Therefore, it is necessary to integrate multicultural values ​​in religious education to strengthen social harmony. This study emphasizes the importance of synergy between religion and multiculturalism in building an inclusive and harmonious society in Indonesia.